Bahasa Minangkabau dan Dialek Negeri Sembilan: Satu Tinjauan Perbandingan Linguistik Historis Komparatif - Reniwati Reniwati (Jurnal Elektronik WACANA ETNIK, 2012)
Negeri Sembilan was one of temporary and permanent residence abroad. The migration went on in 14th century.  The influence of this might be looked at the sociocultural Negeri Sembilan today including at their dialect.  In this paper will be explained the comparison between the Minangkabau language and Negeri Sembilan dialect. The purpose of this is to review the relation of that isolect. To achieve them, the analyzing of data will apply the lexicostatistics that is one of the methods in historical comparative of linguistics.